PENGEMBANGAN PERMAINAN ROLE PLAY GAME UNTUK MENDUKUNG PEMBELAJARAN PERAKITAN PERANGKAT KERAS KOMPUTER - Sukirman, Sukirman; Hernawan, Dicky (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2024)
This study aims to develop an innovative educational tool in the form of game with genre RPG (Role Playing Game) to support the learning of computer hardware assembly in vocational high schools (SMK). Utilizing the Multimedia Development Life Cycle (MDLC) method, the development process consists of six stages: conceptualization, design, material collection, component integration, testing, and distribution. The game is designed with map-based missions simulating real-life computer assembly scenarios, using RPG Maker MV as the primary platform. The participants involved in this study consisted of 25 students, including 9 males and 16 females, aged 16–17 years. The instrument used for data collection was the User Experience Questionnaire (UEQ), which employs a questionnaire to evaluate the level of user experience across six variables. Based on the analysis conducted, most variables were categorized as "Excellent," with scores of 2.60 (Attractiveness), 2.50 (Perspicuity), 1.77 (Efficiency), 1.62 (Dependability), 2.50 (Stimulation), and 2.37 (Novelty). Thus, it can be concluded that the developed RPG game can be effectively used to support learning in computer assembly.